Laser-Induced Evoked Potentials in the Brain after Nonperceptible Optical Stimulation at the Neiguan Acupoint: A Preliminary Report. (17th April 2012) - Litscher, Gerhard; Bauernfeind, Guenther; Mueller-Putz, Gernot; Neuper, Christa
Abstract : We report on small but reproducible human cerebral evoked potentials after bilateral nonperceptible laser needle (658 nm, 40 mW, 500  μ m, 1 Hz) irradiation of the Neiguan acupoint (PC6). The results which are unique in scientific literature were obtained in a 26-year-old female healthy volunteer within a joint study between the Medical University of Graz, the Karl-Franzens University of Graz, and the Graz University of Technology. The findings of the 32-channel evoked potential analysis indicate that exposure to laser needle stimulation with a frequency of 1 Hz can modulate the ascending reticular activating system. Further studies are absolutely necessary to confirm or refute the preliminary findings.